2013
DOI: 10.1016/j.oooo.2013.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Stable gene-silence of Kif2a synergistic with 5-fluorouracil suppresses oral tongue squamous cell carcinoma growth in vitro and in vivo

Abstract: Our data support that Kif2a is a potential molecular target for the therapeutics of recurrent and metastatic SCCOT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…A previous study demonstrated that the silencing of KIF2A significantly inhibits the growth and invasion of oral tongue squamous cell carcinoma, which suggested that KIF2A may regulate the viability and invasion of cancer cells (29). In the present study, 5-8F cell proliferation decreased and apoptosis increased in the KIF2A siRNA group compared with the control groups.…”
Section: Discussionsupporting
confidence: 57%
“…A previous study demonstrated that the silencing of KIF2A significantly inhibits the growth and invasion of oral tongue squamous cell carcinoma, which suggested that KIF2A may regulate the viability and invasion of cancer cells (29). In the present study, 5-8F cell proliferation decreased and apoptosis increased in the KIF2A siRNA group compared with the control groups.…”
Section: Discussionsupporting
confidence: 57%
“…The prevalence of elevated KIF2A expression was increased in lymphoma tissues compared with reactive hyperplasia, indicating that KIF2A may contribute to the malignant transformation of DLBCL. These observations are consistent with those from other tumors [ 11 , 20 , 21 ]. Additionally, the overexpression of KIF2A was related to Ann Arbor stage and high-risk IPI stratification in patients with DLBCL.…”
Section: Discussionsupporting
confidence: 93%
“…Another study showed that overexpression of KIF2A promoted metastasis and invasion of SCCOT, indicating that KIF2A overexpression is unfavorable for predicting the prognosis of SCCOT [ 20 ]. Notably, both in vivo and in vitro, treatment with KIF2A RNAi remarkably enhanced the sensitivity of SCCOT cells to 5-FU [ 21 ], suggesting that targeting KIF2A can overcome drug resistance and improve the treatment of tumors. In human epithelial ovarian cancer, overexpression of KIF2A was found in tumor tissues, and KIF2A conferred increased invasive and metastatic potential to tumor cells [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…KIF2A is a member of the kinesin families involved in cell mitosis and spindle assembly that is commonly recognized as being associated with human neuronal diseases . In recent years accumulated evidence has defined the oncogenic role of KIF2A in multiple human cancers, such as breast cancer, glioma and squamous cell carcinoma . In our study the oncogenic role of KIF2A in human gastric cancer was newly discovered.…”
Section: Discussionmentioning
confidence: 65%